The Conservation of Uncertainty. - Armour, Phillip G. (Communications of the ACM, 2007)
This article reports on the relevance and importance of being able to measure software in a variety of methods. The author asserts that as software is in itself a knowledge acquisition activity, software designers should understand the building blocks of upon which it is designed even though the processes have been vastly simplified. Line of code (LOC) writing is now supported with robust languages tools and pre-built components, and the author contends this is a good decoupling of knowledge discovery from knowledge delivery, but the knowledge content of a accelerated production process is inherently diminished.